Cathode/anode integrated composite bipolar plate for high-temperature PEMFC. (1st May 2017) - Lee, Dongyoung; Lim, Jun Woo; Lee, Dai Gil
Abstract: Carbon fiber reinforced polymer composites are ideal substitutes for the brittle graphite bipolar plate in lightweight proton exchange membrane fuel cells (PEMFCs) because of their high specific strength and stiffness. Among the various types of carbon composite bipolar plates, non-woven carbon felt based composites have recently attracted attention because they require much lower curing pressures than unidirectional carbon fiber or carbon fabric composites. In this work, a carbon felt composite bipolar plate is developed for a high-temperature PEMFC (HT-PEMFC) using randomly oriented non-woven carbon felt and a cyanate ester-modified epoxy. The cathode and anode are integrated into a single bipolar plate to reduce the thickness and weight of the HT-PEMFC stack. The developed composite bipolar plate exhibits superior electrical properties because of the bare carbon fibers exposed on the surface by the soft layer method. In addition, the bipolar plates are dimensionally stable under high-temperature and high-pressure conditions. Finally, a cell test is performed on a 3-cell HT-PEMFC stack to investigate the cell performance.